The entitled nation: how people make themselves white in contemporary England - Garner, Steve (Sens public, 2010)
The way ‘race’ shapes the lives of the ethnic majority (i.e. white Europeans) has not been a major focus of sociological research. Our findings, drawn from extensive interviews are that middle and working-class white Britons share concerns about resource allocation and perceived cultural threats, which express themselves in racialised discourse. However, the concerns are often articulated through classed experiences, and revolve around feelings of entitlement. These feelings link people who are socially and economically under-privileged to those who are much wealthier in economic and cultural capital. In the imaginary ‘hierarchy of entitlement’ people are sorted according to the contribution made, so those seen as newcomers (principally non-white immigrants) as well as those white locals who do not contribute are placed at the bottom.